Primary Graft Dysfunction - Natalini, Jake G.; Diamond, Joshua M. (Seminars in Respiratory and Critical Care Medicine, 2021)
Primary graft dysfunction (PGD) is a form of acute lung injury after transplantation characterized by hypoxemia and the development of alveolar infiltrates on chest radiograph that occurs within 72 hours of reperfusion. PGD is among the most common early complications following lung transplantation and significantly contributes to increased short-term morbidity and mortality. In addition, severe PGD has been associated with higher 90-day and 1-year mortality rates compared with absent or less severe PGD and is a significant risk factor for the subsequent development of chronic lung allograft dysfunction. The International Society for Heart and Lung Transplantation released updated consensus guidelines in 2017, defining grade 3 PGD, the most severe form, by the presence of alveolar infiltrates and a ratio of PaO2:FiO2 less than 200. Multiple donor-related, recipient-related, and perioperative risk factors for PGD have been identified, many of which are potentially modifiable. Consistently identified risk factors include donor tobacco and alcohol use; increased recipient body mass index; recipient history of pulmonary hypertension, sarcoidosis, or pulmonary fibrosis; single lung transplantation; and use of cardiopulmonary bypass, among others. Several cellular pathways have been implicated in the pathogenesis of PGD, thus presenting several possible therapeutic targets for preventing and treating PGD. Notably, use of ex vivo lung perfusion (EVLP) has become more widespread and offers a potential platform to safely investigate novel PGD treatments while expanding the lung donor pool. Even in the presence of significantly prolonged ischemic times, EVLP has not been associated with an increased risk for PGD.
Keywords: primary graft dysfunction; ischemia–reperfusion injury; lung transplantation